A research agenda for international agricultural trade - Martin, Will (Oxford University Press, 2018)
International trade is likely to be a hugely important and interesting area for research by agricultural and applied economists in the next decade. While the questions for research are likely to change—with less emphasis on large-scale international negotiations and more on national reforms and regional agreements—there will be important challenges in understanding the driving forces for world agricultural markets, in trade policy, and in ensuring food security. New analytical techniques built on the gravity model and geospatial production data create many opportunities for innovative applications and expand the range of questions to which researchers in this field can effectively respond.